2016
DOI: 10.1186/s12890-016-0185-5
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria infect different cell types in the human lung and cause species dependent cellular changes in infected cells

Abstract: BackgroundMycobacterial infections remain a significant cause of morbidity and mortality worldwide. Due to limitations of the currently available model systems, there are still comparably large gaps in the knowledge about the pathogenesis of these chronic inflammatory diseases in particular with regard to the human host. Therefore, we aimed to characterize the initial phase of mycobacterial infections utilizing a human ex vivo lung tissue culture model designated STST (Short-Term Stimulation of Tissues).Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 73 publications
2
48
0
Order By: Relevance
“…Our results are distinct from those with Mycobacterium tuberculosis or M . marinum where neutrophils appear to be less mobilized [34,38]. Ex vivo infections of human lung tissues indicated that neutrophils had a greater tendency to phagocytize Mabs than M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are distinct from those with Mycobacterium tuberculosis or M . marinum where neutrophils appear to be less mobilized [34,38]. Ex vivo infections of human lung tissues indicated that neutrophils had a greater tendency to phagocytize Mabs than M .…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo infections of human lung tissues indicated that neutrophils had a greater tendency to phagocytize Mabs than M . tuberculosis and that Mabs has a higher capacity to induce the migration of neutrophils than other mycobacterial species [38]. Additionally, while neutrophils are unable to kill virulent strains of M .…”
Section: Discussionmentioning
confidence: 99%
“…The first method (Fig. 4A) begins with surface decontamination, followed by dissection of tissues into cubes of approximately equal sizes [59,239]. In pigs, surface decontamination could be carried out by briefly searing the ventral surface of the pleura (< 1s) with a hot pallet knife [239].…”
Section: Ex Vivo Lung Modelmentioning
confidence: 99%
“…Similar techniques are also applicable to lung tissues from human donors. In a recent study, a human ex vivo lung tissue culture model was used to characterize the initial phase of mycobacterial infections and it was discovered that the infection of different cell types in early mycobacterial infections is bacteria species dependent [59]. Unfortunately, the ex vivo lung model prepared following this procedure also has limitations, the most important of which is the high variance in the data obtained, which most likely resulted from tissue heterogeneity and inconsistent cutting.…”
Section: Ex Vivo Lung Modelmentioning
confidence: 99%
“…In a report of ex vivo human lung tissue infected with M. tuberculosis, M. avium and M. abscessus, Ganbat et al [32], found macrophages, neutrophils, monocytes, and pneumocytes-II infected with mycobacteria and nuclear alterations resulting in cell death depending on the mycobacterial species used. This system provides a similarity to the original lung microenvironment with its native cell population, orientation, and structural integrity.…”
Section: Researchers Have Also Infected Pclts With Different Viruses mentioning
confidence: 99%